Factors Influencing Relationships in Malay Family - Harun, Y. (Scottish Group of Education and Testing Services, 2014)
The discussion in this paper focuses on the factors that influenced family relationships in Malay society. There are six major factors identified namely: age, seniority, power and authority, gender, collateral distance, marriage, residential patterns and family obligations. Emphasis is given to the role of Islam and Malay kinship system in determining the nature of those relationships. Islam is the core element of Malay culture, and Islamic principles have become the guiding principles for social organizations, activities, and relationships, including family relationships among the Malays. Kinship system also provides the basis for family organizations and relationships, but its principles should not contradict those of Islam. Otherwise both sets of principles are allowed to co-exist.